(untitled) (Research, Society and Development, 2021)
Ethnopharmacological relevance: Diabetes mellitus is a disease that affects approximately 10% of the world population. As it is a chronic disease, several patients search for alternatives to the traditional allopathic treatment, such as medicinal plants. In Brazil, the Aspidosperma subincanum (Guatambu) is one of the vegetal species commercialized in open markets used for diabetes popular treatment. Objective: To perform the phytochemical prospection and pre-clinical assessment of the ethanolic extract from stem bark of A. subincanum bark (EEAS). Material and methods: A. subincanum stem barks were collected in state of Goiás, Brazil and the EEAS was obtained by cold maceration. The phytochemical prospection was performed and acute and subacute toxicity assessments were performed according to OECD guidelines. Results: Phytochemical prospection identified the presence of steroids, triterpenes, saponins, tannins, alkaloids, coumarins, and resins. The acute toxicity showed no death in EEAS doses administered intraperitoneally (500, 1000, and 2000 mg/kg) and orally (5000 mg/kg). The subacute toxicity showed signs of nephrotoxicity, hepatotoxicity, and lung damages in the two highest doses tested (250, 250 mg/kg) in a dose-dependent way. However, the satellite group showed reversion of the lesions after 30 days of EEAS interruption. Conclusion: The acute toxicity of EEAS suggests an LD50 > 5000 mg/kg. The oral use of EEAS during a short period (30 days) or more can be hazardous at doses similar to that tested in this study and may represent a risk for those who consume this kind of extract as a medicinal plant.